Theoretical and experimental investigation on heating moving packed beds in a single tube with constant wall temperature. (December 2021) - Yu, Yupu; Nie, Fuliang; Bai, Fengwu; Wang, Zhifeng
Highlights: Deriving the thermal resistance of the heating process of moving packed beds. Proposing a heat transfer model for the heating of moving packed beds. Experimental results of electrically heating moving packed beds validate the heat transfer model. The influence of parameters provides suggestion for the design of moving packed beds heating devices. Abstract: Moving packed beds based on solid particles are receiving increasing attention in high temperature applications for their stability and wide range of working temperatures. A heat transfer model is proposed to describe the heat transfer behavior of moving packed beds. The model incorporates the pseudo-continuum character of moving packed beds and the discrete nature of the solid particles by dividing the moving packed bed into bulk and near-wall regions. The bulk region was considered as a pseudo-continuum described by a convective thermal resistance. Inside the near-wall region, the discrete characteristics of the solid particles are taken into account while only heat transfer through the solid material and the interstitial gas was included. The thermal resistance of the near-wall region was considered as a contact thermal resistance in series with a convective thermal resistance. In this paper, the heat transfer of moving packed beds with two heated section lengths was tested for four kinds of flow rates. By comparing with experimental results, it's verified that the model can describe the heat transfer behavior of moving packed beds over a wide range of particle flow rates. From a parameter sensitivity analysis, it's found that increasing the particle flow rate has an opposite effect on the heat transfer rates. A higher particle flow rate will simultaneously increase the contact thermal resistance and reduce the convective thermal resistance. With the increase of the particle flow rate, the heat transfer rate starts to decline when the effect of the increasing contact thermal resistance grows beyond the effect of the improved convection. In addition, for longer residence time heat transfer processes, the convective thermal resistance is the primary influence factor. But for shorter residence time heat transfer processes, the contact thermal resistance becomes the main thermal resistance. The proposed model could be used in the design of industrial-scale moving packed bed heating devices.